2020
DOI: 10.3390/met10020292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SLM Processing Parameters on Microstructures and Mechanical Properties of Al0.5CoCrFeNi High Entropy Alloys

Abstract: Selective laser melting (SLM) to fabricate Al0.5CoCrFeNi high entropy alloys with pre-mixed powders was studied in this paper. The influences of process parameters including laser power, scanning speed, and hatch spacing on the relative density of high-entropy alloys (HEAs) were investigated. A relative density of 99.92% can be achieved by optimizing the SLM process parameters with laser power 320 W, scanning speed 800 mm/s, and hatch spacing of 60 μm, respectively. Moreover, the microstructure of the HEAs was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Fujieda et al [371] found SLM-built Co 1.5 CrFeNi 1.5 Ti 0.5 Mo 0.1 HEA exhibited excellent tensile strength of 1178.0 MPa and elongation of 25.8 % due to smaller grain size and the homogenous structure without any intermetallic compounds, which was further improved after post-heat treatment [371]. In another studies, superior mechanical properties of Al 0.3 CoCrFeNi and Al 0.5 CoCrFeNi HEA fabricated by SLM were reported by [377][378][379]. The ductility of AlCrCuFeNi x HEA manufactured using SLM improved with the increase in Ni content [354].…”
Section: Laser-processed Heasmentioning
confidence: 90%
“…Fujieda et al [371] found SLM-built Co 1.5 CrFeNi 1.5 Ti 0.5 Mo 0.1 HEA exhibited excellent tensile strength of 1178.0 MPa and elongation of 25.8 % due to smaller grain size and the homogenous structure without any intermetallic compounds, which was further improved after post-heat treatment [371]. In another studies, superior mechanical properties of Al 0.3 CoCrFeNi and Al 0.5 CoCrFeNi HEA fabricated by SLM were reported by [377][378][379]. The ductility of AlCrCuFeNi x HEA manufactured using SLM improved with the increase in Ni content [354].…”
Section: Laser-processed Heasmentioning
confidence: 90%
“…Similarly, at low laser power and higher scan speed, a lack of fusion defects is more pronounced due to a lack of energy input to fully melt the powder layer [29,35,56]. Sun et al [57] showed the relationship between the part density and input energy density for Al0.5CoCrFeNi High Entropy Alloys (Figure 6). It can be observed that for lower energy density, the highest porosity is reported.…”
Section: Origin Of Defectsmentioning
confidence: 98%
“…Energy Density (J/mm 3 ) Figure 6. Relative density as a function of energy density [57]. Reused under Creative Commons Attribution License.…”
Section: Relative Density (%)mentioning
confidence: 99%
“…Similarly, at low laser power and higher scan speed, a lack of fusion defects is more pronounced due to a lack of energy input to fully melt the powder layer [29,35,56]. Sun et al [57] showed the relationship between the part density and input energy density for Al0.5CoCrFeNi High Entropy Alloys (Figure 6). It can be observed that for lower energy density, the highest porosity is reported.…”
Section: Origin Of Defectsmentioning
confidence: 99%